Determination of Ka values for some phenolic compounds derived from benzoyl acetonitril by electrical conductivity - Adil Saeed Azooz; Mohammad Mahmood Hasan Alnaemi; Raed Tariq Alabadi (مجلة التربية والعلم, 2013)
Abstract This investigation was started by synthesis of three phenolic Schiff bases from the mother compound benzoyl acetonitril, These having OH groups in o، m، p positions on amino side of molecules. The structures of these imines were confirmed from U.V. and I.R. spectra as well as melting points. The main object of the study is the determination of Ka values for these mentioned imines at temperature rang (25 - 65)oC by conductivity measurement method. The method as found, simple, precise and accurate. At any constant temperature, acidities of imines were observed in different order of arrangements. Finally the thermodynamic parameters of ionization reactions of acids were calculated and discussed in details.